Do Patients Demonstrate Improved Patient-Reported Outcome Measures Following Revision Shoulder Arthroplasty Relative to Their Pre-Primary Condition? A Retrospective Case Series - Justin Leal; Eoghan T. Hurley; Lulla Kiwinda; Mikhail Bethell; Samuel G. Lorentz; Sean P. Ryan; Christopher S. Klifto (HSS Journal®: The Musculoskeletal Journal of Hospital for Special Surgery, 2026)
Background: No study has evaluated patient-reported outcome measures (PROMs) from before primary total shoulder arthroplasty (TSA) to after revision TSA to determine if patients felt that they were better off than prior to undergoing primary TSA. Understanding this longitudinal trajectory could help guide clinical decision-making and set realistic patient expectations regarding the potential benefits of revision TSA. Purposes: The purpose of this study was to compare PROMs of patients prior to initial TSA to after revision TSA to determine if they were better off relative to their pre-primary TSA condition. Methods: A single center was retrospectively reviewed to identify patients who underwent revision TSA from May 1, 2013, to February 1, 2024. All patients’ charts were reviewed to collect their primary procedure date and indication. Only patients who underwent anatomic or reverse TSA were included. Pre-primary and post-revision generic PROMs were subsequently collected. Patients who did not have pre-primary and post-revision PROMs collected were excluded. Median pre-primary and post-revision PROMs were then compared. Results: A total of 62 patients were included. After revision TSA, patients had lower median Patient-Reported Outcome Measure Information System (PROMIS) pain interference scores than before their primary TSA (62.0 [55.2-66.8] vs 66.5 [63.0-72.0]) and 66.1% achieved minimum clinically important difference (MCID). Median PROMIS physical function post-revision was higher than pre-primary TSA scores (38.0 [32.0-44.0] vs 30.5 [27.0-36.0]) and 61.3% achieved MCID. Conclusion: The findings of this retrospective case series suggest that patients who have been revised for complications after TSA showed improved PROMs relative to their pre-primary TSA condition. Level of Evidence: Level IV, retrospective case series.